Religious Pluralism from the Catholic Point of View - Kubacki, Zbigniew Józef (Verbum Vitae, 2021)
The question about how religious pluralism should properly be understood from the Catholic point of view has been asked since the outset of Christianity. It was also formulated in the context of A Document on Human Fraternity for World Peace and Living Together signed by Pope Francis and the Grand Imam of Al-Azhar, Ahmad Al-Tayyeb. The present article gives a theological interpretation of the sentence included in the Abu Dhabi document: “The pluralism and the diversity of religions, color, sex, race and language are willed by God in His wisdom, through which He created human beings.” It argues that this passage should be understood correctly within the inclusivist paradigm that recognizes and confers to non-Christian religions and to religious pluralism a status de iure without jeopardizing the foundations of Catholic faith: the unicity and salvific universality of Jesus Christ and the Church. In conclusion, the question concerning the application of the assertion to the case of Islam has been explored.